1999
DOI: 10.1038/10338
|View full text |Cite
|
Sign up to set email alerts
|

The lack of chromosomal protein Hmg1 does not disrupt cell growth but causes lethal hypoglycaemia in newborn mice

Abstract: High mobility group 1 (HMG1) protein is an abundant component of all mammalian nuclei, and related proteins exist in all eukaryotes. HMG1 binds linear DNA with moderate affinity and no sequence specificity, but bends the double helix significantly on binding through the minor groove. It binds with high affinity to DNA that is already sharply bent, such as linker DNA at the entry and exit of nucleosomes; thus, it is considered a structural protein of chromatin. HMG1 is also recruited to DNA by interactions with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
376
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(389 citation statements)
references
References 26 publications
9
376
0
Order By: Relevance
“…319 Targeted disruption of hub genes Trrap, Rere or Hmgb1 in the mouse leads to pre-or perinatal lethality. [320][321][322] Hsp90, which encodes a 90-kDa member of the heat-shock protein family, is also thought to have a role in the suppression or buffering of mutations, 323,324 possibly through chromatin modification of genes in the Wnt signaling pathway. 325 HSP genes are important for responses to inflammation and toxic environmental stressors.…”
Section: Epigenetic Regulation and Autismmentioning
confidence: 99%
“…319 Targeted disruption of hub genes Trrap, Rere or Hmgb1 in the mouse leads to pre-or perinatal lethality. [320][321][322] Hsp90, which encodes a 90-kDa member of the heat-shock protein family, is also thought to have a role in the suppression or buffering of mutations, 323,324 possibly through chromatin modification of genes in the Wnt signaling pathway. 325 HSP genes are important for responses to inflammation and toxic environmental stressors.…”
Section: Epigenetic Regulation and Autismmentioning
confidence: 99%
“…HMGB-1 modulates the activities of nuclear targets, including p53, steroid hormone receptors, glucocorticoid receptor, and homeobox proteins. HMGB-1 is essential for ex utero growth and survival; HMGB-1 knockout mice fail to survive more than 24-48 hours postpartum (10).…”
Section: Hmgb-1 As a Nuclear Dna Binding Protein And Membrane-associamentioning
confidence: 99%
“…The intrinsic capacity of HMGB1 for altering DNA structures allows it to participate in many biological processes like regulation of chromatin structure, 9 transcription, 10 DNA damage repair and recombination processes. 11 Recent cell biology and biochemical studies indicated that HMGB1 is actively involved in modulating the efficiency of all four major DNA repair pathways, i.e.…”
mentioning
confidence: 99%